2019
DOI: 10.1101/845511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative and functional genomics analysis of the genusRomboutsiaprovides insight into adaptation to an intestinal lifestyle

Abstract: 24Cultivation-independent surveys have shown that the recently described genus Romboutsia within the 25 family Peptostreptococcaceae is more diverse than previously acknowledged. The majority of 26Romboutsia-associated 16S rRNA gene sequences have an intestinal origin, but the specific roles that 27Romboutsia species play in the digestive tract are largely unknown. The complete genomes of the 28 human intestinal isolate Romboutsia hominis FRIFI T (DSM 28814) and the soil isolate Romboutsia 29 lituseburensis A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 111 publications
3
49
0
Order By: Relevance
“…Moreover, the genome analysis of Romboutsia spp. showed that this genus contains a versatile array of metabolic capabilities related to carbohydrate utilization and fermentation of single amino acids (Gerritsen, 2015). Moreover, E. coprostanoligenes is documented to have the capability of removing the cholesterol (Freier et al, 1994), and Acetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genome analysis of Romboutsia spp. showed that this genus contains a versatile array of metabolic capabilities related to carbohydrate utilization and fermentation of single amino acids (Gerritsen, 2015). Moreover, E. coprostanoligenes is documented to have the capability of removing the cholesterol (Freier et al, 1994), and Acetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…As work on these species has not been conducted in poultry, mapping of the human intestinal microbiome demonstrates that Romboutsia spp. is present in nutrient-rich environments where exogenous sources of amino acids and vitamins are abundantly available [ 27 ]. Whilst there is limited literature on this species functionality in poultry, the carbon sources it utilizes include D-arabinose, L-fucose, D-galactose, D-glucose, raffinose, and sucrose and it can produce acetate and formate [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romboutsia (OTU5) had a high abundance in the jejunum across age compared to the colon. The genus Romboutsia associates with carbohydrate utilization, fermentation of amino acids and anaerobic respiration [43]. Clostridiales (OTU20), which had high abundances across all ages in the jejunum, is a saprophytic organism that ferments plant polysaccharides.…”
Section: Biogeography Dissimilarities Of Gut Microbiotamentioning
confidence: 99%